Joan Procter, Dragon Doctor: The Woman Who Loved Reptiles - Valdez, Patricia; Sala, Felicita (New York Alfred A. Knopf, 2018)
A picture-book biography of the early 20th-century woman who became the Curator of Reptiles at the British Museum and went on to design the Reptile House at the London Zoo.
Includes bibliographical references.
Keywords: Procter, Joan -- Juvenile literature; Procter, Joan; London Zoo (London, England) -- Juvenile literature; London Zoo (London, England); Zoo keepers -- Biography; Reptiles -- Juvenile literature. -- Research; Zoo keepers; Reptiles